Taufiqul Hakim â€œAmtsilatiâ€ dan Pengajaran Nahwu-sharaf - M Misbah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
One of skill becoming goals in study Arabic Ianguage reading skill. Someone wish to reach it must mastering various interconnected knowledge, among others Nahwu â€“Sharaf. This knowledge becomes burden to one whom studying it especially for beginner. This because the huge number of items exist in Nahwu-Sharaf, so that need very long time to mastering it. This Items effectiveness and time efficiency represent the problem in Nahwu-Sharaf learning. These matters become Taufiqul Hakimâ€™s study materials and concern. Finally he found one new format of efficient and effective method and items in learning Nahwu-Sharaf. The Items compiled in his books entitled â€œBuku Amtsilatiâ€ and his method knows as Amtsilati Method. The application of Amtsilati Method in Nahwu â€“ Sharaf learning emphasize the student activeness, with rather few theory but much practice and also delivering items start from easy then gradually reaching difficult ones.